Effect of Competence, Communication and Job Stress Towards Service Quality PT. Sukses Motor Globalindo - Rahmat Alamsyah Harahap; Friska Priscilla; Meiliani Wijaya; Shellin (Journal of Research in Business, Economics, and Education, 2020)
PT. Sukses Motor Globalindo is an official dealer of Honda H1, H2, H3. The problems in the company were the quality of employee services were less spry, certainty in getting services was lacking, the ease of choosing the desired unit has not been fulfilled. The problems of employee’s competence were lack of support for solving the problems and solutions, lack of initiative on every job. The problem of communication was the information conveyed by the leader was not precisely addressed to whom, did not understand the flow of conversation and organizational culture. The problem of job stress were the employees got pressure into stress causing the employees to become uncomfortable and affect the quality of employee services to internal and external parties. The research method used was the quantitative descriptive, the nature of research was the explanatory   research.   Population   of   50   respondents, using   saturated   sampling 30 respondents tested the validity and reliability of PT. Buana Jaya Lestari. The result of determination coefficient test obtained Adjusted R Square of 0,464, this means that competence, communication and job stress affect to the quality of service with a level of 46.4%, while the remaining 53.6% were other factors such as infrastructure, reliability and responsiveness